Antigen-specific immune reactions by expanded CD8+ T cell clones from HLA-B*27-positive patients with spondyloarthritis. Issue 133 (December 2022) - Deschler, Katharina; Rademacher, Judith; Lacher, Sonja M.; Huth, Alina; Utzt, Markus; Krebs, Stefan; Blum, Helmut; Haibel, Hildrun; Proft, Fabian; Protopopov, Mikhail; Rodriguez, Valeria Rios; Beltrán, Eduardo; et al.
Abstract: Spondyloarthritis (SpA) is a chronic inflammatory disease that is tightly linked to HLA-B*27 but the pathophysiological basis of this link is still unknown. It is discussed whether either the instability of HLA-B*27 molecules triggers predominantly innate immune reactions or yet unknown antigenic peptides presented by HLA-B*27 induce adaptive autoimmune reactions by CD8 + T cells. To analyze the pathogenesis of SpA, we here investigated the T cell receptor (TCR) usage and whole transcriptomes of CD8 + single cells from synovial fluid of HLA-B*27-positive SpA patients and HLA-B*27-negative controls. In HLA-B*27-positive patients, we confirmed preferential expression of several TCR β-chain families, found even more restricted usage of particular TCR α-chains, assigned matching TCR αβ-chain pairs with homologous CDR3-sequences, and detected identical TCR-chains in different patients. Gene expression analyses by single cell mRNAseq revealed that genes specific for the tissue resident memory phenotype, exhaustion, and apoptosis were particularly highly expressed in expanded clonotypes from HLA-B*27-positive SpA patients. Together, several independent lines of evidence argue in favor of an (auto)antigenic peptide related pathogenesis. Highlights: Spondyloarthritis (SpA) is tightly linked to the expression of HLA-B*27. The T cell receptor (TCR) repertoire is shaped by MHC molecules, here by HLA-B*27. Strong biases of CD8 + TCR alpha- and beta-chain expression specific to SpA patients. Tissue resident memory phenotype, exhaustion and apoptosis of CD8 + T cells in SpA. Data argue in favor of arthritogenic peptides presented by HLA-B*27 to CD8 + T cells.